On the control strategy to improve the salt rejection of a thin-film composite reverse osmosis membrane - Lee, Jaewoo (2022)
Since the specific energy consumption (SEC) required for reverse osmosis (RO) desalination has been steeply reduced over the past few decades, there is an increasing demand for high-selectivity membranes. However, it is still hard to find research papers empirically dealing with increasing the salt rejection of RO membranes and addressing the SEC change possibly occurring while increasing salt rejection. Herein, we examined the feasibility of the process and material approaches to increase the salt rejection of RO membranes from the perspective of the SEC and weighed up a better approach to increase salt rejection between the two approaches. A process approach was confirmed to have some inherent limitations in terms of the trade-off between water permeability and salt rejection. Furthermore, a process approach is inappropriate to alter the intrinsic salt permeability of RO membranes, such that it should be far from a fundamental improvement in the selectivity of RO membranes. Thus, we could conclude that a material approach is necessary to make a fundamental improvement in the selectivity of RO membranes. This paper also provides discussion on the specific demands for RO membranes featuring superior mechanical properties and excellent water/salt permselectivity to minimize membrane compaction while maximizing the selectivity.